A distribute and self-tuning wireless environment monitoring system for buildings based on the Wi-Fi Direct technology. (2nd January 2018) - Yu, Hao; Zhang, Jili
Abstract : As the quality of building energy management systems has been taken seriously by more and more people, finding an efficient way to gather and release information for the system is of great importance. Compared with the wired monitoring system, the wireless system has many advantages, such as flexibility and economy, when applied in buildings. However, most wireless monitoring systems are composed of nodes with different functions and the communication protocols are not standard or transparent, which, therefore, is difficult to track the malfunctions and complicated for unprofessional users. In order to promote standardization of wireless networks applied in buildings and making it easier to manage and extend, the current article has developed a self-organized wireless network based on the Wi-Fi Direct technology to monitor the environment for large-scale buildings. In this network, all the nodes are identical in function and the communication is based on the Transmission Control Protocol/Internet Protocol. A distribute data processing mechanism to rectify the outliers is utilized in the network. The performance of the proposed network has been testified through both simulations and experiments. The results have shown that the proposed monitoring system has advantages, such as dynamic in structure, easy to extend, transparent in communication, and distributed in data processing.